Correction to - Nseir, Saad (2021)
Following publication of the original article [1], the authors identified an error in the Abstract and Results section. The correct numbers and text are given hereafter. Abstract VAP was associated with significantly higher risk for 28-day mortality in SARS-CoV-2 group (adjusted HR 1.65 (95% CI 1.11–2.46), p = 0.013), but not in influenza (1.74 (0.99–3.06), p = 0.052), or no viral infection groups (1.13 (0.68–1.86), p = 0.63). Results Primary and secondary outcomes: VAP was associated with higher risk for 28-day mortality in in SARS-CoV-2 group, but not in the two other groups (Fig. 2A). All the changes that were requested are implemented in this correction and the original article [1] has been corrected.